Keep Calm and Be Happy: A Mixed Method Study from Character Strengths to Well-being - EKŞİ, HALİL (EDAM, 2018)
The purpose of this study is to investigate the characteristics and sources of a peaceful and happy life. The research uses the sequential exploratory design from the mixed research designs. The grounded theory design has been used in the qualitative part of the study. In-depth interviews were performed in the qualitative section with 26 participants between the ages of 21 and 82. The structural equation model has been used in the quantitative section of the study. A total of 900 participants (548 women) between the ages of 18 and 75 (M - 30.46, SD 12.94) form the sample of the study. According to the findings from the qualitative stage of the research. peaceful and happy living means having comfort and positive feelings and not having negative feelings. In spite of peace and happiness being related to each other and intertwined, peace is understood to be more permanent, prioritized, and significant compared to happiness. Sufficiency in relationships and trust, personal virtues, social virtues, acceptance. spirituality. developmental strength of problems, optimism, nature, health and economics, as well as activities and superficial solutions constitute the sources of peace and happiness. The quantitative stage of the research has found peace and happiness to positively correlate with the characteristics of tolerance. helpfulness. beliefs and spirituality, responsibility, purposefulness, worthiness, trust, and reliability. Relationships among the variables have been tested using different structural equation models. The research results are considered to contribute to the literature on positive psychology and its applications.
Keywords: Peace; Happiness; Values; Character strengths; Grounded theory; Structural equation model; POSITIVE PSYCHOLOGY; SELF-COMPASSION; LIFE SATISFACTION; POSTTRAUMATIC GROWTH; COUNTING BLESSINGS; NATURE RELATEDNESS; MENTAL-HEALTH; HAPPINESS; KINDNESS; CONCEPTIONS